2002
DOI: 10.1310/6177-qdjj-56du-0nw0
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Aided Neurorehabilitation: From Evidence-Based to Science-Based Rehabilitation

Abstract: There is no "magic bullet" in rehabilitation. In the absence of direct neural transplants, neurological rehabilitation is an arduous process. We have pioneered the clinical application of robotics in stroke rehabilitation and have shown evidence of the positive impact of targeted exercise on stroke recovery. In this article, we will review results obtained in the initial clinical trials with 96 stroke patients at the Burke Rehabilitation Hospital. We will provide evidence that robot-aided training enhances rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(100 citation statements)
references
References 17 publications
5
93
1
1
Order By: Relevance
“…Considering that the second motor task did not make provision for an auditory cue for the catching/ returning movements, the patients could not be driven to execute faster movements than they would normally have executed, and therefore, velocity indices could not be used to reveal functional motor outcome improvements. Previous studies concerning robotic rehabilitation approaches in stroke patients have reported improved proximal arm functions (Burgar et al, 2000;Krebs et al 2002), but did not show an optimal motor recovery of the distal motor segments of the upper limb, which are involved in most ADL (Wisneski and Johnson, 2007). Conversely, arm weight support rehabilitation leads to reduced NJ and to increased hand RoM, which is crucially important for positive recovery of upper limb motor control (Morasso, 1981;Wisneski and Johnson, 2007), and possibly related to improved functional ability in executing ADL.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Considering that the second motor task did not make provision for an auditory cue for the catching/ returning movements, the patients could not be driven to execute faster movements than they would normally have executed, and therefore, velocity indices could not be used to reveal functional motor outcome improvements. Previous studies concerning robotic rehabilitation approaches in stroke patients have reported improved proximal arm functions (Burgar et al, 2000;Krebs et al 2002), but did not show an optimal motor recovery of the distal motor segments of the upper limb, which are involved in most ADL (Wisneski and Johnson, 2007). Conversely, arm weight support rehabilitation leads to reduced NJ and to increased hand RoM, which is crucially important for positive recovery of upper limb motor control (Morasso, 1981;Wisneski and Johnson, 2007), and possibly related to improved functional ability in executing ADL.…”
Section: Discussionmentioning
confidence: 95%
“…This study examined the effectiveness of rehabilitation training performed with or without an arm weight sup- Although previous studies conducted in chronic stroke patients have reported an increased functional motor gain after arm-weight support device training (Krebs et al, 2002;Macclellan et al, 2005;Sanchez et al, 2006;Masiero et al, 2007;Colombo et al, 2008;Kwakkel et al, 2008), the present study was the first to be conducted during the acute phase after stroke, using kinematic analysis to evaluate upper limb motor performance. It is strongly suggested in the literature that the acute phases following neurological damage are the most sensitive to approaches designed to exploit neural plasticity (Paolucci et al, 2000;Dobkin, 2004), particularly the first six months after stroke (Paolucci et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Krebs et al, 1998) These measures are currently being used as powerful tools in a quantitative, science-based approach to the study of recovery from neurological injury. (Krebs et al, 2002) These benefits make it desirable to distribute stroke robots and make them as widely available as possible. Not only would this provide better therapy and more complete recovery to a larger population, but it would also allow for the collection of recovery data on a larger group of subjects and increase the rehabilitation community's understanding of the progression of therapy, which in turn would allow for therapy better matched to the patient, which would lead to more complete recovery, etc.…”
Section: Current State Of the Art In Physical Therapy Roboticsmentioning
confidence: 99%